Bronze Age Textiles of the North Cemetery: Discoveries made by the Franco-Chinese Archaeological Mission in the Taklamakan desert, Xinjiang, China - Cardon, Dominique; Debaine-Francfort, Corinne; Idriss, Abdulressul; Anwar, Khasim; Xingjun, Hu (Archaeological Textiles Review, 2013)
A cemetery dated to the Middle to Late Bronze Age (c. 1700 BC and earlier), recently excavated by the Franco-Chinese Archaeological Mission in the Taklamakan desert, Xinjiang, north-west China, is the source of more than one hundred different textiles. The background of the North Cemetery excavation and its context within a survey of ancient sites among the dried-up deltas of the Keriya River are described here by the directors of the Mission, Corinne Debaine-Francfort and Abduressul Idriss. The second part of the article is a catalogue by Dominique Cardon et al. of all the artefacts found in one of only two intact burials found by the Mission which had been left undisturbed by looters. This complete assemblage gives a very good idea of the range of textiles originally present across the cemetery. It also provides a striking comparison with the textiles found at another Bronze Age site, Xiaohe or Small River, near to Lopnor and about 600 km to the east of the North Cemetery (Xiaohe, has recently been re-excavated by Abduressul Idriss; the textiles from the Folke Bergman’s original excavation were published in 1941 by Vivi Sylwan but at that time were undated).